มาตรการในการช่วยเหลือไม่ให้ลูกหนี้ซึ่งเป็นบุคคลธรรมดาต้องล้มละลาย - เกียรติศักดิ์ ภมรไมตรี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The economic crisis in Thailand has caused many juristic persons and individuals to face financial difficulties, or not being able to pay back their debts to the creditor on time. Therefore, the Bankruptcy Act has added a restorative process which can help juristic persons to continue with their business with out facing bankruptcy. On the other hand, individuals are still bound by the Bankruptcy Act to go bankrupt. Under consideration that the debtors are foundation of country’s economic, and they have the capability to pay back their debts, forcing them to bankruptcy does not indeed beneficial to the society. The objective of this thesis is to explore the concept of measure to protect individuals from bankruptcy. From researches in bankruptcy laws of the United States and the United Kingdom, it is found that both contain measures to assist individuals to have debt management, similar to juristic persons. The measures allow court to use judgment in ordering debt management, postponement of due-date, as well as limitation to the persons’ right involved in the debt compromise. However, the research shows Thai Bankruptcy Act assistance only applies to those juristic persons. This limitation means that it is an incomplete process to protect all debtors. From the equity point of view, individuals should receive the same kind of assistance similarly to juristic persons under the same Bankruptcy Act. Consequently, this thesis proposes an approach to enact measures to protect individuals from bankruptcy as follows: 1. To set qualification for individuals debt owner. 2. To set standards for appointing debt handler for individuals. 3. To propose a way to create process to protect individuals from bankruptcy. 4. To set standard in cancellation of such protective measure. In conclusion, this thesis proposes an additional measure to assist a debtor to make a compromise with one’ creditor before facing bankruptcy.